GREEN SYNTHESIS OF SILVER NANOPARTICLES USING THE LEAF EXTRACT OF PUTRANJIVA ROXBURGHII WALL. AND THEIR ANTIMICROBIAL ACTIVITY. - Ghazanfar Ali, Syed; Khan, Haris M; Jalal, Mohammad; Azam Ansari, Mohammad; Mahdi, Abbas Ali; Ahmad, Mohammad Kaleem (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: This study deals with the synthesis of silver nanoparticles (AgNP's) from the extract of the leaves of the plant Putranjiva roxburghii wall. Using biological method, i.e., green synthesis. Methods: The extract from the leaves acts as a reducing and stabilizing agent for the AgNP's. Further characterization was done using various techniques like ultraviolet (UV)-visible spectrophotometry, which shows surface plasmon resonance, Fourier transform infra-red spectroscopy analysis shows formation of various bonds, scanning electron microscope (SEM) and transmission electron microscope (TEM) analysis depicts the distribution and average size of nanoparticles. The antimicrobial activity was also checked against various bacteria and fungi using minimum inhibitory concentration and well diffusion assay. Result: UV analysis shows strong plasmon resonance between 420 and 480 nm SEM analysis shows the distribution of synthesized nanoparticles, whereas TEM analysis shows the average particle size to be near about 5 nm and well diffusion assay proved that these nanoparticles are effective against different microorganisms. Conclusion: P. roxburghii wall. shows strong potential for the reduction of silver from Ag+ to Ag0 and nanoparticles so formed are strongly active against various microorganism. Keywords: Putranjiva roxburghii, Fourier transform infra-red, Scanning electron microscope, Transmission electron microscope.